The Effectiveness of the Work Environment at the Makassar City Public Works Office - Nasrullah, Muh.; Wulandari, Wulandari; Yusdiana, Helda; Jamaluddin, Jamaluddin; Djamaluddin, A. (Universitas Negeri Makassar, 2021)
This study is a quantitative descriptive study that aims to determine how the effectiveness of the work environment at the Makassar City Public Works Office. The total population in this study was 186 respondents with a sample of 65 respondents using the Probability Sampling technique sampling technique, namely Simple Random Sampling. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique used is descriptive percentage and distribution analysis. The results showed that the effectiveness of the work environment at the Makassar City Public Works Office was classified as effective in terms of the indicators of the working atmosphere classified in the effective category, including clear light or lighting, quiet and quiet sound, safety at work, sufficient temperature to control. affect employee performance. Indicators of relationships with co-workers are classified as very effective, including relationships with co-workers that are harmonious, kinship and without mutual intrigue among co-workers. Work Facilities are categorized as effective including equipment or complete work facilities, one of which supports smooth work.